2016
DOI: 10.1111/jan.12964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a quality care‐metric on public health nursing practice: protocol for a mixed methods study

Abstract: This study will evaluate the impact of introducing a quality care-metric into public health nursing practice. Results will illuminate the quality of public health nursing practice in relation to the primary visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Awareness of PHNs’ work environment challenges could facilitate effective management, improve patient outcomes, and enhance daily organizational capacity (Graham et al., 2011). Measuring nursing processes could identify where resources are required to improve the work environment and ultimately care quality (Cusack et al., 2014; Giltenane et al., 2016; Butler et al., 2019). Limited resources and limited managerial or clinical support have been shown to impact negatively on quality improvement using process performance indicators (Cusack et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Awareness of PHNs’ work environment challenges could facilitate effective management, improve patient outcomes, and enhance daily organizational capacity (Graham et al., 2011). Measuring nursing processes could identify where resources are required to improve the work environment and ultimately care quality (Cusack et al., 2014; Giltenane et al., 2016; Butler et al., 2019). Limited resources and limited managerial or clinical support have been shown to impact negatively on quality improvement using process performance indicators (Cusack et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement using quality indicators plays an integral role in improving the quality of care provided (Giltenane et al., 2016). Quality Care‐Metrics (QCMs) measure the quality of nursing processes and are informed by evidence‐based standards internationally (Giltenane et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The private obstetric led option remains popular amongst those who can afford the cost. (13) found that over a six-year period between 2005-2010 30.3% of all maternities had booked for privately. However, this gure steadily decreased to 24.2% over the six years.…”
Section: Introductionmentioning
confidence: 99%
“…Follow up postnatal appointment(s) are arranged with their obstetrician, in a clinic style setting. Despite women being signi cantly more likely to have an obstetric intervention irrespective of obstetric risk factors, private obstetric led care remains the only viable option for many women to ensure continuity of carer in Ireland (13,15).…”
Section: Introductionmentioning
confidence: 99%